Web streaming e suas vertentes - Santos, Tamires Cardoso dos (2019)
This research is a reflection on WebTv, through the method of observation and immersion of cartography. This research proposed a theoretical survey about this area, and an analysis of the different approaches to the fields of creation, production and distribution of Web TV content, Live and On Demand (previously recorded content that people has access). The research had as function to reveal the potentialities of this medium. The main justification for this proposal was the timeliness of the theme and the few researches done about it. This doctoral dissertation aims to continue what the master's dissertation was, resuming exactly where it left off. For this, a case study on OktoTv was performed. With this study, we intend to advance the studies on WebTv as this case study can be taken as a referral to think about the creation of a model project. The conclusion contains considerations to which the research led us, ending with insertions of new questions and future projects. The result of this research we observe that it is still a field in full development, and extremely changeable